Law Enforcement on Misuse of Personal Data by Online Loan Business Actors - Linus Ndruru; Carolus Wahyu Herman; Deny Octa Ttistian; Sigit Widodo (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to explore data breaches in the usage of online loan applications (peer-to-peer lending) that happen as a result of financial advancements in technology. It is essential to discuss the issue of personal data security in online loan application activities because it concerns fundamental privacy for everyone. This phenomenon not only offers convenience in obtaining loan facilities but also creates problems, primarily related to personal data entered during registration and requests for access to several points of personal data when making loans through the application provided and vulnerable to being misused by third parties and even the platform. Alone. Based on the findings of normative juridical investigations conducted, borrowers' data is legally protected under the ITE Law and OJK regulations governing financial technology (fintech). In addition, administrative sanctions and criminal sanctions can be applied if personal data is violated. If an online lending business actor violates someone's data, the district court will sanction the customer or cybercrime perpetrator and revoke the fintech business license from the financial services authority (OJK)